THE TURN OF THE SCREW - James, Henry, 1843-1916; Mackenzie, Fiona; Grebtsova, Natalia; Pitts, Sorrel (London : Penguin Books, 2021)
"A young woman accepts her first job as a governess and goes to Bly, a large country house in England. There she teaches a young brother and sister. But the governess soon starts to see ghosts and tries to protect the children from them"--Back cover
Includes questions and excercises
Keywords: Governesses -- Juvenile fiction; Children stories, English; England -- Juvenile fiction